Interior of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the principal east-facing entrance to the garbhagriha (sanctum sanctorum) of the Bhandasar Temple. The original fabric of this entrance has been enveloped in golden embossing. The pilasters, doorway, and dvarashakha (architrave) are adorned with golden meenakari (enamel) work. Intricate details of the floral motifs cover the entire surface of the entrance. The wooden doorway has attendants painting on it.